Stress and mental health at work: a guide for union reps - Oates, Andrea (London, 2016)
"Stress is one of the main factors causing work-related ill-health. A growing number of union reps are voicing their concerns as low pay, job insecurity, precarious forms of employment and huge job cuts have left many struggling to cope.